EFEKTIVITAS ASESMEN DIAGNOSTIK DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Wiji Listiyani; Barokah Isdaryanti; Wiwi Isnaeni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The diversity of students’ characteristics, learning readiness, and prior knowledge in elementary schools often presents challenges for teachers in designing effective and inclusive learning processes. One strategy promoted in recent educational reforms is the implementation of diagnostic assessment, which functions to identify students’ learning needs before instruction begins. This study aims to analyze the role of diagnostic assessment in improving the quality of learning in elementary schools. The research employed a Systematic Literature Review (SLR) method by examining 20 references published within the last five years, consisting of books and scientific articles indexed in Scopus and SINTA. The review process involved identifying, selecting, evaluating, and synthesizing relevant literature related to diagnostic assessment and learning quality improvement. The findings indicate that diagnostic assessment contributes significantly to improving instructional quality by helping teachers identify students’ cognitive and non-cognitive conditions, adapt learning strategies, differentiate instruction, and provide appropriate learning support. Furthermore, diagnostic assessment encourages more student-centered learning, increases engagement and participation, and supports the achievement of learning objectives more effectively. The synthesis of the reviewed studies also shows that the successful implementation of diagnostic assessment depends on teachers’ assessment literacy, institutional support, and the availability of valid assessment instruments. Therefore, diagnostic assessment can be considered a strategic approach to creating adaptive, inclusive, and meaningful learning experiences in elementary education. The results of this review provide recommendations for educators and policymakers to strengthen the integration of diagnostic assessment into classroom learning practices to enhance educational quality.